2020
DOI: 10.1002/biot.201900571
|View full text |Cite
|
Sign up to set email alerts
|

Production of Substituted Styrene Bioproducts from Lignin and Lignocellulose Using Engineered Pseudomonas putida KT2440

Abstract: Please refer to published version for the most recent bibliographic citation information. If a published version is known of, the repository item page linked to above, will contain details on accessing it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 33 publications
0
23
0
Order By: Relevance
“…New methods are being implemented to isolate these components from sugarcane bagasse, bark trees and kraft lignin obtained from the pulp and paper industries. These methods can involve chemical and physical approaches, such as hydrolysis and extraction, or bacterial action [ 31 , 32 , 33 , 34 , 35 ]. An alternative method could be that of resorting to synthetic biology to valorize lignin and biosynthesized coumarins [ 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…New methods are being implemented to isolate these components from sugarcane bagasse, bark trees and kraft lignin obtained from the pulp and paper industries. These methods can involve chemical and physical approaches, such as hydrolysis and extraction, or bacterial action [ 31 , 32 , 33 , 34 , 35 ]. An alternative method could be that of resorting to synthetic biology to valorize lignin and biosynthesized coumarins [ 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, itaconic acid, a chemical building block listed among the top 12 value-added chemicals, was also produced from p-coumaric acid by the engineered Pseudomonas strain [159,160]. In addition, the engineered Pseudomonas strain accumulated and converted p-coumaric/ ferulic acid into 4-vinylphenol/4-vinylguaiacol, which were further applied to polymerize 4-vinylguaiacol and 4-vinylcatechol styrene by the enzymatic reaction of T. versicolor laccase [161].…”
Section: Bioconversion Of Lignin Derivative Into Bio-based Chemicals and Materialsmentioning
confidence: 99%
“…2021, 11, x FOR PEER REVIEW 22 of 31 [159,160]. In addition, the engineered Pseudomonas strain accumulated and converted pcoumaric/ ferulic acid into 4-vinylphenol/4-vinylguaiacol, which were further applied to polymerize 4-vinylguaiacol and 4-vinylcatechol styrene by the enzymatic reaction of T. versicolor laccase [161]. These results showed that bioconversion processes for lignin valorization could be potential cell factories for the production of a variety of renewable chemicals and materials through metabolic engineering and synthetic biology technology.…”
Section: Bioconversion Of Lignin Derivative Into Bio-based Chemicals and Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although some organisms, such as Pseudomonas putida and Streptomyces mobaraense, have been used for the production of 4VP from glucose [ 7 , 27 ] or grass lignin feedstocks [ 28 ], the production of 4VP from CA has been attempted primarily in E. coli . Here we explored whether other bacterial species could be more tolerant to higher, more industrially relevant concentrations of substrate and product and to the presence of an organic overlay for product extraction.…”
Section: Introductionmentioning
confidence: 99%